Caring through distancing: Spatial boundaries and proximities in the cystic fibrosis clinic. (November 2020) - Buse, Christina; Brown, Nik; Nettleton, Sarah; Martin, Daryl; Lewis, Alan
Abstract: This paper re-examines relations between proximity, distance and care, focusing on practices of 'distancing' in the cystic fibrosis (CF) clinic. While care is often thought of in terms of proximity, literature on 'landscapes of care' highlights the potential for 'care at a distance'. We extend this literature to examine practices of social distancing, specifically the act of maintaining a 'space between' bodies in communal areas – a practice currently brought to the fore by the COVID-19 pandemic. Using the CF clinic as a case study, we examine how distancing can be understood as an emplaced practice of care, shaped by – and shaping - architectures and materialities in particular contexts. We explore these issues drawing on data from Pathways, practices and architectures: containing antimicrobial resistance in the cystic fibrosis clinic, a UK AHRC funded study (AH/R002037/1) examining practices in three cystic fibrosis clinics using visual and ethnographic methods. Clinical staff practices of maintaining distancing were often regarded by patients as 'care-ful', part of personalised 'care in place', embroiling a wider care assemblage including ancillary staff, materialities and architectures. Patients also actively participate in distancing as an 'ethic of care', using strategies of 'holding back' and 'looking out' in confined spaces. Yet our findings also highlight tensions between care, proximity and distance in circulation spaces and communal areas, including transient spaces where the assemblage of care breaks down. The article concludes by considering wider implications for healthcare design and for the COVID-19 pandemic. Highlights: Distancing constitutes an emplaced practice of care in cystic fibrosis clinics. CF patients engage in distancing as part of an 'ethic of care'. Practices of distancing require support from a wider 'care assemblage'. Distancing can be constrained or enabled by architectures and materialities.